Designing Multicolor Graphics of Plasmonic Metasurfaces through Gradual Protrusion of Particles at Free Interface. Issue 7 (3rd February 2022) - Kim, Minjung; Kim, Jong Bin; Lee, Seung Yeol; Nam, Seong Kyeong; Kim, Shin‐Hyun
Abstract: Metal nanostructures show plasmonic colors in the absence of pigments, which are promising for various optical applications. Colloidal lithography is one of the cost‐effective methods for a wide‐area production of plasmonic metasurfaces. However, it remains an important challenge to regioselectively control plasmonic property in a facile and reliable manner. Here, a novel strategy is reported to produce multicolor plasmonic graphics using the gradual protrusion of colloids at a water‐resin interface. Particles anchored at free interfaces slowly migrate toward the equilibrium position. Therefore, the degree of protrusion into the opposite phase is determined by the duration of aging. With this phenomenon, dimple arrays with controlled depths is produced by capturing the particles at the water‐resin interface through photopolymerization and removing the particles. Directional deposition of aluminum on the dimple arrays renders plasmonically colored surfaces, where the resonant wavelengths, or colors, vary with dimple depth. As the resin is regioselectively photocurable by ultraviolet irradiation through photomasks, plasmonic graphics can be produced. In addition, multi‐steps of regioselective photocuring with controlled durations of incubation produce multicolor graphics. The graphics show consistent plasmonic colors for specular reflection while displaying iridescent diffraction colors from hexagonal arrays of dimples for off‐specular conditions, enhancing the visibility of graphics. Abstract : Multicolor graphics of plasmonic metasurfaces are created from templates of particle‐decorated water‐resin interfaces. Dimple arrays are produced by polymerizing the resin and removing the particles, which is plasmonically colored by aluminum deposition. As particles gradually protrude at free interfaces, the dimple geometry is controllable with incubation time, which enables the tuning of plasmonic colors and the production of multicolor patterns.